GE_GERICHTE C/9510/2016 vom 25. Juni 2019 - GE Cour de justice (2019)
ACTION EN JUSTICE;SERVITUDE DE CONDUITES NÉCESSAIRES;AGGRAVATION DE LA SERVITUDE;INTERPRÉTATION(SENS GÉNÉRAL);FRACTIONNEMENT | CC.730.al1; CC.731; CC.738; CC.743.al1; CC.974b; CC.739